As expressões do patriarcado e do capitalismo nos atos de alienação parental no âmbito do núcleo Ceará-Mirim, da Defensoria Pública do Rio Grande do Norte - Cardoso, Márcia Maria Martins da Silva (2018)
Presents an analysis of the expressions of patriarchy and capitalism in cases involving acts of parental alienation in the context of the Public Defender's Office in Rio Grande do Norte (DPE/RN), Core of Ceará-Mirim. Thus, from a critical perspective, historicaldialectic, the approach contemplates the historical contextualization and dynamics of social relationships that involve the determinants of parental alienation, interwoven in the expressions of the Patriarchate/ capitalism. To do so, uses theoretical references, statistics, analysis of documents, conducted research and institutional on DPE/RNCore of Ceará-Mirim. The survey was comprised of two stages: the first featured 30 interviews, applied to 15 men and 15 women, ex-couples. The cases were selected from statements made on DPE/RN about acts of parental alienation, in which women were victims of the above-mentioned acts. Such criterion was given, since most scholars point the parent and the children, as victims of parental alienation, and the mother, usually the guardian of the child, such as alienation. The second stage has selected 10 of the 15 previous cases; however, the new interviews were applied only to women, with a diverse sample, in relation to parental alienation suffered form; sexual orientation; race/ethnicity; time of separation; current marital status and type of child custody. After the tabulation and data analysis, the results show that most of the men interviewed agree that: 1) a woman's place is at home taking care of the children; 2) custody of the child/teenager should stay with the parent who has greater financial condition; 3) the woman who betrays should lose custody of the child to the parent; 4) the stepfather should not reside in the same environment of stepdaughters; 5) lesbian women should not get custody of the children. In addition to the above, it was possible to identify feelings of jealousy and revenge, from the end of the relationship, as well as competitiveness, selfishness, stuck in the culture of ownership and male domination. In research conducted with women was found that the former running campaign of disqualification of maternal behaviour, hinder the exercise of parental authority, as well as the approach of mother to the children, standing in the exercise of rights regulated coexistence familiar. It is concluded that the acts of parental alienation are expressions of the Patriarchate/capitalism and also configure how violence against women.